THE INFLUENCE OF ESOP (EMPLOYEE SHAREHOLDING PROGRAM), GOOD CORPORATE GOVERNANCE, INTEREST RATES, EXCHANGE RATES, INFLATION, DEFERRED TAXES ON FINANCIAL PERFORMANCE IN PROPERTY AND REAL ESTATE COMPANIES ARE LISTED ON THE INDONESIA STOCK EXCHANGE - Bramanto Wijaya; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (SEAN Institute, 2023)
The purpose of this study was to examine and analyze the effect of ESOP (Employee Stock Ownership Program), Good Corporate Governance, Interest Rates, Exchange Rates, Inflation, Deferred Taxes on Financial Performance in Property and Real Estate Companies listed on the Indonesia Stock Exchange. The population in this study were 65 Property and Real Estate Companies listed on the Indonesia Stock Exchange for the period 2018-2020. The sample of this research is 27 financial statements of property and real estate companies listed on the Indonesia Stock Exchange for the period 2018-2020. This study uses multiple linear regression analysis. The results showed that the ESOP (Employee Stock Ownership Program) had no effect on the Financial Performance of Property and Real Estate Companies listed on the Indonesia Stock Exchange. INSD has no effect on the Financial Performance of Property and Real Estate Companies listed on the Indonesia Stock Exchange. INST has no effect on the Financial Performance of Property and Real Estate Companies listed on the Indonesia Stock Exchange. Public ownership has no effect on the Financial Performance of Property and Real Estate Companies listed on the Indonesia Stock Exchange. Exchange Rates have no effect on Financial Performance in Property and Real Estate Companies listed on the Indonesia Stock Exchange. Inflation has no effect on the Financial Performance of Property and Real Estate Companies listed on the Indonesia Stock Exchange. Deferred Tax has no effect on the Financial Performance of Property and Real Estate Companies listed on the Indonesia Stock Exchange. ESOP (Employee Stock Ownership Program), Good Corporate Governance, Exchange Rate, Inflation, Deferred Tax have no effect on Financial Performance in Property and Real Estate Companies listed on the Indonesia Stock Exchange.